Emotional Intelligence, Teamwork and Knowledge Management: A Causal Model on Public Service Motivation among Healthcare Workers in Region XI - Audan, Dr. Ricardo; Bandiola, Dr. Alberto N (American Journal of Public Policy and Administration, 2024)
Purpose: Public service motivation, a pivotal factor in driving healthcare professionals to contribute to societal welfare, faces significant threats (Perry & Vandenabeele, 2015; Perry & Ritz, 2022). Globally, healthcare workers grapple with issues like staff shortages, excessive work hours, and escalating stress levels, culminating in burnout and a potential decline in service quality (Buchan, 2020; Agence France-Presse, 2021; Mendoza, 2021; Irandoost et al., 2022; Vejdani, 2021). It is for this reason that this study is conducted to establish a structural equation model of public service motivation by developing a theoretical framework explaining the relationships between various factors contributing to public service motivation, such as emotional intelligence, teamwork, and knowledge management. Materials and Methods: Four hundred forty three healthcare workers were selected through proportional stratified sampling. A validated and approved adapted survey questionnaire was disseminated through google form. This study was a quantitative, descriptive research project using structural equation modeling approach. Understandably, the data analysis used mean and standard deviation, Pearson r, multiple regression analysis, and structural equation modeling techniques to test the proposed theoretical framework and identify the relationships between the different constructs. IBM SPSS was utilized to analyze the data. Findings: The healthcare workers have a high level of emotional intelligence, teamwork, knowledge management, and public service motivation. There is a significant correlation between the exogenous and endogenous latent variables. In the context of this study on Public Service Motivation, Model 5 has been designated as the best-fit model based on rigorous statistical validation and theoretical consistency. Under emotional intelligence, Appraisal and Expression in the Self and Regulation of Emotion remained. In Teamwork, Mutual Support and Team Structure remained. In Knowledge Management, Training and Mentoring, Knowledge Capture, Incentives, Leadership, and Policies remained, and under Public Service Motivation, Self-sacrifice, and Commitment to Public Interest remained in the model. Therefore, the findings of the study would be not only for the government health care workers but for the private as well. Recommendations: Healthcare workers must be provided with training programs focused on improving emotional intelligence which can equip them with the skills to understand better and manage their emotions, improving job satisfaction and motivation; regular team-building activities to enhance collaboration, improve communication, and foster a supportive work environment; and create a knowledge-sharing system, promoting continuous learning, and providing regular training updates. In addition, they must be a system to Recognize and reward healthcare professionals for their efforts and promoting a healthy work-life balance, providing mental health resources, and ensuring manageable workloads to help maintain their high motivation levels. In Portugal, it is valuable for healthcare workers to attend to training programs to capacitate them as professionals (Amaral et al., 2022). Finally, policy makers must revisit existing systems and practices on public service motivation to be able to assess what needs to be developed for policy improvement.